If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 12 = 14 + -9x Reorder the terms: 12 + 4x = 14 + -9x Solving 12 + 4x = 14 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 12 + 4x + 9x = 14 + -9x + 9x Combine like terms: 4x + 9x = 13x 12 + 13x = 14 + -9x + 9x Combine like terms: -9x + 9x = 0 12 + 13x = 14 + 0 12 + 13x = 14 Add '-12' to each side of the equation. 12 + -12 + 13x = 14 + -12 Combine like terms: 12 + -12 = 0 0 + 13x = 14 + -12 13x = 14 + -12 Combine like terms: 14 + -12 = 2 13x = 2 Divide each side by '13'. x = 0.1538461538 Simplifying x = 0.1538461538
| 5x+8=4+3x | | (16x^2+20x-6)/(2x^2-9x-56) | | (5x+2)(2x^2-9x-5)=0 | | 2(y-4)=-4y-10 | | x+3(x+3)=10 | | (100/4)^-1/2 | | 7-4x=-6x+1 | | 6=x+1/x | | -7x^2+24-9=0 | | 4x/2x | | 8(x-9)=7 | | 2x+6x=12 | | 2c+6c+8+=32 | | 3(2+1)=8 | | (4x-1)/(2x^2-3) | | -2x+6=-x+5 | | =11m-3n-3s | | 2x^2-8+3=0 | | 12x-1+2x=x+1 | | -12+27x=-12 | | 10x+10x=118+x | | -3x^2-8x+35=0 | | 1x^2-5x-12=0 | | 5-2x=3x-50 | | 1/3(10x-5)=8 | | 12x=-9-4x^2 | | 1x^2+5x-10=0 | | 20x^2-66x-14=0 | | 1x^2+1x-30=0 | | 2x+1=4.5 | | x+(x+1)=156 | | -7x+7x=+1 |